Dampak Keberadaan Lingkungan Bendungan Titab terhadap Sosial Ekonomi Petani dan Lingkungan di Kecamatan Seririt - ARIASTUTI, NI KADEK ERNI; ANTARA, MADE; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
The Impact of Titab Dam Development on Socio-Economic Aspect of Farmers and the Environmental Aspect in Seririt District Titab Dam is built to meet the needs and supply of irrigation water. The purpose of this study is to identify social impact, analyze economic impact, and estimate the environmental impact of the development of Titab Dam on farmers in the Seririt District. Titab Dam in Seririt District has no social impact on farmers, measured by five parameters consisting of ease of water for irrigation, ease of raw water, better irrigation networks, agricultural institutions existence, and conflict of irrigation water. Titab Dam in Seririt District has no economic impact on farmers, measured by four parameters consisting of the quantity of harvest, farmer's income, production costs, and consumption water costs. Titab Dam in Seririt District has no environmental impact, measured by six parameters consisting of water for agriculture and ecosystems, land erosion, multiplication of crops planted, agricultural land loss for the construction of the Titab Dam, crop productivity and land productivity. Farmers are suggested to be wise in using water sources for irrigation. Managers and the government need to optimize the function of the dam through the management system. Future studies on Titab Dam are still needed.